How we made the world a better place : kids and teens write on how they changed their corner of the world - Fairview Press (Minneapolis, Minn. : Fairview Press, 1998)
A collection of essays in which kids and teenagers write about the things they have done to change the world for the better, inspired by a contest sponsored by Fairview Press.
Voice of Youth Advocates (V.O.Y.A.).
Young Adult
Keywords: Child volunteers -- United States -- Case studies; Helping behavior in children -- United States -- Case studies; Young volunteers -- United States -- Case studies; Helping behavior -- Case studies; Volunteer work -- Case studies